2004
DOI: 10.17221/3685-pse
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rapeseed stand density on the formation of generative organs

Abstract: This experiment was carried out for the study of differences in dynamics of formation and reduction of generative organs from the beginning of the flowering to the harvest, under different stand density of the winter rapeseed. The evaluation of the results of the study of stand density, confirms that from the technological point of view it is appropriate to choose a thinner population of rapeseed. Starting with the stand density of 60 plants/m 2 we do not observe significant differences in plants during the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Data values estimated the calculated seed yield to about 800 grams per square meter. Such value corresponds to the calculated seed yield in the study by Kuchtová and Vašák (2004). As only a small sample size was used for this test, the data remain only indicative.…”
Section: Resultsmentioning
confidence: 83%
“…Data values estimated the calculated seed yield to about 800 grams per square meter. Such value corresponds to the calculated seed yield in the study by Kuchtová and Vašák (2004). As only a small sample size was used for this test, the data remain only indicative.…”
Section: Resultsmentioning
confidence: 83%
“…Alam, (2004); Vujaković et al, (2014) reported that high plant population (low row spacing) had significant effect on plant height. In contrast, Kuchtova and Vasak, (2004) found that high plant population had no significant effect on plant height. Also Fathi et al, (2002) showed that high plant population had decreased number of silique per plant and weight of thousand seed.…”
mentioning
confidence: 85%
“…Buds, flowers and siliques of winter rape fall down more from lateral branches than from terminal, which is more preferred [62]. Similarly fruit size decline from margin to the centre of capitulum as the result of resource competition [86,1].…”
Section: Seed Development and Influence Of The Seed On The Plant Growthmentioning
confidence: 99%